T2 quantification in brain using 3D fast spin‐echo imaging with long echo trains. Issue 5 (11th December 2021) - Snyder, Jeff; McPhee, Kelly C.; Wilman, Alan H.
Abstract: Purpose: Three‐dimensional fast spin‐echo (FSE) sequences commonly use very long echo trains (>64 echoes) and severely reduced refocusing angles. They are increasingly used in brain exams due to high, isotropic resolution and reasonable scan time when using long trains and short interecho spacing. In this study, T 2 quantification in 3D FSE is investigated to achieve increased resolution when comparing with established 2D (proton‐density dual‐echo and multi‐echo spin‐echo) methods. Methods: The FSE sequence design was explored to use long echo trains while minimizing T 2 fitting error and maintaining typical proton density and T 2 ‐weighted contrasts. Constant and variable flip angle trains were investigated using extended phase graph and Bloch equation simulations. Optimized parameters were analyzed in phantom experiments and validated in vivo in comparison to 2D methods for eight regions of interest in brain, including deep gray‐matter structures and white‐matter tracts. Results: Phantom and healthy in vivo brain T 2 measurements showed that optimized variable echo‐train 3D FSE performs similarly to previous 2D methods, while achieving three‐fold‐higher slice resolution, evident visually in the 3D T 2 maps. Optimization resulted in better T 2 fitting and compared well with standard multi‐echo spin echo (within the 8‐ms confidence limits defined based on Bland‐Altman analysis). Conclusion: T 2 mapping using 3D FSE with long echo trains and variable refocusing angles provides T 2 accuracy in agreement with 2D methods with additional high‐resolution benefits, allowing isotropic views while avoiding incidental magnetization transfer effects. Consequently, optimized 3D sequences should be considered when choosing T 2 mapping methods for high anatomic detail.